Geomorphological Study of the Samigaluh Area and Its Surroundings, Kulon Progo Regency, Yogyakarta - Fadea Risa Azzahra; Budhi Setiawan (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2025)
Samigaluh District and its surrounding areas, Kulon Progo Regency, Special Region of Yogyakarta, form part of the Kulon Progo Mountains, which lie within the eastern segment of the Southern Serayu Mountains zone. This region exhibits complex geomorphological conditions resulting from the interaction of tectonic activity, volcanism, and ongoing denudational processes. This study aims to provide knowledge and benefits for relevant stakeholders and readers, thereby supporting related scientific fields and areas of expertise. The research method involved field observations combined with analyses using Geographic Information Systems (GIS) and Digital Elevation Model (DEM) data. Geomorphological characteristics were analyzed by correlating drainage patterns, slope gradients, and lithological units to identify landform features within the study area. The results indicate that the geomorphic units in the Samigaluh area consist of Volcanic Denudational High Hills, representing remnants of ancient volcanic edifices that have undergone prolonged weathering and erosion over geological timescales; Intrusive Hills, formed by the intrusion of igneous rocks into surrounding strata and subsequently exposed by erosion; and Karst High Hills, which developed predominantly through carbonate dissolution processes. The diversity of these geomorphic units reflects the strong influence of geological dynamics on the landscape evolution of the study area.